Tschirnhaus reader of Spinoza - Olesti, Josep (Anales del Seminario de Historia de la Filosofía, 2021)
The three main questions that appear in the correspondence between Tschirnhaus and Spinoza are addressed: freedom; the production of bodies from the Extension attribute; the relationship between the modes of the Thought attribute and the modes of the other attributes. The difficulties that Tschirnhaus detects and the value and scope of Spinoza’s answers are analysed.